A Single-Centre Experience of Post-COVID-19 Vaccine-Related Immune-Mediated Complications. (30th September 2022) - Palmer, David; Davis, Lauren; Sivaloganathan, Helena; Chevassut, Timothy
Abstract : The significant impact of the COVID-19 pandemic has resulted in a worldwide effort to develop effective vaccines. In the United Kingdom, the COVID-19 vaccine development and roll-out has been overwhelmingly successful in reducing infections and deaths. However, case reports have emerged of a rare syndrome of vaccine-induced immune thrombocytopenia and thrombosis (VITT), as well as cases of immune thrombocytopenia (ITP). This has necessitated a better understanding of these conditions. However, as both VITT and "vaccine-associated ITP" are emerging conditions, evidence on the clinical features, epidemiology, and management is still evolving. Subsequently, with the initiation of the COVID-19 vaccine booster program, it has become increasingly important to continue to collect accurate data on post-COVID-19 vaccine complications to aid with their prompt recognition and management. In this case series, we report on the presentations and management of seven cases of post-COVID-19 vaccine-related immune-mediated complications which occurred at our center between the months of March and July 2021.